Sistem Transparansi Dana Desa Di Kabupaten Kudus Menggunakan Metode Algorithma Information Retrieval System - Pratomo Setiaji (LPPM, 2018)
Kudus is a district in the province of Central Java. The capital of this district is the City of Kudus, located on the northeast coastline of Central Java between the City of Semarang and the City of Surabaya. The city is about 51 kilometers from the east side of the city of Semarang, Kudus gets a large village fund allocation, the allocation of funds transferred to the village government to support village development in 2017 reached Rp 219.89 billion. The urgency of this study is based on the problems that arise in its use based on the survey including Error mechanism, Not according to plan or unclear allocation, Not according to Guidelines, Guidelines, technical guidelines (especially procurement of goods and services), Administration of financial statements: (Markup and markdown, double counting), Reduction of Village Fund allocations, for example, village funds are used as assets of village heads and tools for personal gain, cannot be held accountable for their use, asset misappropriation: Sale or swap of Kas Desa Village, Rental of Village Cash Land which is not his right. All these problems can be anticipated by presenting good and transparent information with the information system for using village funds (SIMDANDES), the approach method used is a waterfall, for this reason, a Transparency Information System for village fund use (SIMDANDES) is needed for village fund management Gondangmanis Kec. Kab. Kab. Kab. With the Algorithm Information Retrieval System, System (SIMDANDES) method was applied to monitor the use of village funds and their absorption carried out in each village in real time, as well as information for village heads and stakeholders in Kudus District to establish a policy.Keywords: information system, village fund, algorithma information retrieval system